2012
DOI: 10.1007/s10484-012-9191-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of QEEG-Informed Neurofeedback in ADHD: An Open-Label Pilot Study

Abstract: In ADHD several EEG biomarkers have been described before, with relevance to treatment outcome to stimulant medication. This pilot-study aimed at personalizing neurofeedback treatment to these specific sub-groups to investigate if such an approach leads to improved clinical outcomes. Furthermore, pre- and post-treatment EEG and ERP changes were investigated in a sub-group to study the neurophysiological effects of neurofeedback. Twenty-one patients with ADHD were treated with QEEG-informed neurofeedback and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 38 publications
4
114
0
Order By: Relevance
“…As standardization of all procedures is the regular practice in research, we do not have enough empirical data to assure the efficacy of personalized methods planned in accordance with each individual EEG pattern. Nevertheless, recently a small, open-label pilot study showed a significant clinical improvement and electrophysiological normalization after neurofeedback sessions [67]. This is compatible with empirical data showing that different behavioral profiles of children with ADHD present different patterns of EEG activity [34].…”
Section: What Treatment Protocol Is the Best?supporting
confidence: 75%
“…As standardization of all procedures is the regular practice in research, we do not have enough empirical data to assure the efficacy of personalized methods planned in accordance with each individual EEG pattern. Nevertheless, recently a small, open-label pilot study showed a significant clinical improvement and electrophysiological normalization after neurofeedback sessions [67]. This is compatible with empirical data showing that different behavioral profiles of children with ADHD present different patterns of EEG activity [34].…”
Section: What Treatment Protocol Is the Best?supporting
confidence: 75%
“…This seems particularly problematic for QEEG (frequency band) training, whereby recent evidence no longer supports the presumption that increased theta and beta or SMR reduction are reliable ADHD markers (discussed above). These findings question the standard unidirectional "normalization" rationale of QEEG neurofeedback and suggest instead the adoption of bidirectional, 52 individualized, 46,53 or SCP-based regulation approaches. In addition, allowing "probably blinded" rather than strictly blinded measures in the largest studies may well have counterbalanced this bias in this meta-analysis.…”
Section: Methodological Issuesmentioning
confidence: 92%
“…10 Neurofeedback therefore trains users to monitor and change their brainwave patterns, leading to behavioral changes. 11 Some studies have found that neurofeedback can decrease symptoms of ADHD, [12][13][14][15][16][17] including improved attention, 18 behavior, 19 and cognitive improvements 20 up to 6 months postintervention as well as at 2 years postintervention. 21 However, the evidence for its sustainability remains unclear, because there are limited studies examining follow-up data, and those that do have small sample sizes or no control condition.…”
mentioning
confidence: 99%
“…21 However, the evidence for its sustainability remains unclear, because there are limited studies examining follow-up data, and those that do have small sample sizes or no control condition. [13][14][15] In contrast, CT uses specifically designed exercises to train attention, working memory, and impulsivity through ongoing feedback to reinforce correct responses. Several studies suggest that CT improves performance on working memory tasks and decreases inattentiveness, hyperactivity, and disruptive behaviors.…”
mentioning
confidence: 99%